Customer Perception towards E-Banking Services: A Study with Reference to SBI Bank, Mandya City - Savitha, V.; Ranjansathya Das, S. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Electronic banking is the series of technological wonders in the recent past involving use of Internet for delivery of banking products & services. E-Banking is changing the banking industry and is having the major effects on banking relationships. E banking denotes the provision of banking related service through extensive use of information technology without direct resource to the bank by the customer. E-Banking provides various e- channels for using banking services like ATMs, credit cards, debit cards, internet banking, mobile banking, electronic fund transfer (EFT), electronic clearing system etc. The main objective of this research paper includes to understand the theoretical frame work and concept of E-banking services and to highlight the demographic profile of the customers and assess the motivational factors of customers influencing to adoption of E-banking services and also to analyze the satisfaction level of customers regarding e-banking services provided by SBI  Bank, Mandya city.
Keywords: Customer Satisfaction; Debit Card; Demographic Profile; Electronic Banking; Information Technology